2007
DOI: 10.1016/j.dnarep.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of human ribosomal protein S3 to sites of DNA damage is dependant on ERK-mediated phosphorylation following genotoxic stress

Abstract: Besides its role in translation and ribosome maturation, human ribosomal protein S3 (hS3) is implicated in DNA damage recognition as reflected by its affinity for abasic sites and 7, 8-dihydro-8-oxoguanine (8-oxoG) residues in DNA in vitro. Here, we demonstrate that hS3 is capable of carrying out both roles by its ex vivo translocation from the cytoplasm to the nucleus as a consequence of genotoxic stress. The translocation of hS3 is dependent on ERK1/2-mediated phosphorylation of a threonine residue (T42) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
6
59
0
1
Order By: Relevance
“…Our finding of a dose-dependent increase in nuclear localization of RPS3 under conditions of oxidative and UV stress (Fig. 8) is consistent with previous report (17). We did not observe discrete foci formation between RPS3 and RECQL4 possibly because of homogenous RECQL4 expression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our finding of a dose-dependent increase in nuclear localization of RPS3 under conditions of oxidative and UV stress (Fig. 8) is consistent with previous report (17). We did not observe discrete foci formation between RPS3 and RECQL4 possibly because of homogenous RECQL4 expression.…”
Section: Discussionsupporting
confidence: 82%
“…Ribosomal protein S3 (RPS3) is a component of the 40 S ribosomal subunit (16). However, nuclear localization of RPS3, with or without different stimulations (including hydrogen peroxide, methyl methane sulfonate, and TNF) has been reported (17)(18)(19). A mass spectrometry study revealed RPS3 as an interaction partner of WRN (20).…”
mentioning
confidence: 99%
“…In both yeast and humans, RpS3 has enzymatic activity on a variety of damaged DNA substrates generated by UV and oxidative stress (Jung et al 2001;Hegde et al 2004). In humans, RpS3 translocates to the nucleus from the cytosol after phosphorylation by ERK1/2 in cells exposed to oxidative stress and colocalizes with 8-oxoG foci in the nucleus (Yadavilli et al 2007). Titration of free RpS3 by overexpressed Ltv1DNES might deleteriously affect growth if free extraribosomal RpS3 plays a role in DNA surveillance and, hence, in cell division in yeast.…”
Section: Does Titration Of Rps3 Affect An Extraribosomal Function?mentioning
confidence: 99%
“…The rpS3 protein is phosphorylated by extracellular signal-regulated kinase (ERK), a MAP kinase known to play important roles in the regulation of cell growth (6). The phosphorylation event mediated by ERK1/2 is necessary for rpS3 nuclear translocation in response to DNA damage (2). Kim et al have also reported that rpS3 has endonuclease activity, which is increased by protein kinase C delta (PKCδ)-dependent phosphorylation upon exposure to genotoxic stresses (3).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, rpS3 has been shown to have additional extraribosomal functions, such as DNA repair, gene transcription, and apoptosis (2)(3)(4)(5). The rpS3 protein is phosphorylated by extracellular signal-regulated kinase (ERK), a MAP kinase known to play important roles in the regulation of cell growth (6).…”
Section: Introductionmentioning
confidence: 99%